Direct Spectroscopy for Probing the Critical Role of Partial Covalency in Oxygen Reduction Reaction for Cobalt-Manganese Spinel Oxides - Long, Xinghui (Nanomaterials (Basel), 2019)
Nanocrystalline multivalent metal spinels are considered as attractive non-precious oxygen electrocatalysts. Identifying their active sites and understanding their reaction mechanisms are essential to explore novel transition metal (TM) oxides catalysts and further promote their catalytic efficiency. Here we report a systematic investigation, by means of soft X-ray absorption spectroscopy (sXAS), on cubic and tetragonal Co(x)Mn(3-x)O(4) (x = 1, 1.5, 2) spinel oxides as a family of highly active catalysts for the oxygen reduction reaction (ORR). We demonstrate that the ORR activity for oxide catalysts primarily correlates to the partial covalency of between O 2p orbital with Mn(4+) 3d t(2g)-down/e(g)-up, Mn(3+) 3d e(g)-up and Co(3+) 3d e(g)-up orbitals in octahedron, which is directly revealed by the O K-edge sXAS. Our findings propose the critical influences of the partial covalency between oxygen 2p band and specific metal 3d band on the competition between intermediates displacement of the ORR, and thus highlight the importance of electronic structure in controlling oxide catalytic activity.